Failure Factors among Young Entrepreneurs in Higher Education Institution: A Study from Telkom University - Cut Irna Setiawati; Abi Atarita (Bina Nusantara University, 2018)
The purpose of this research was to determine factors that caused the failure of young entrepreneurs in Telkom University among the participants of 2016-2017 competition and exhibition. This research applied a quantitative method with a descriptive and explorative research type. Techniques of collecting data were using questionnaires. This research used the nonprobability sampling method that was saturated sampling because of all members of the population of 116 respondents in this research. Data analysis was using Principal Component Analysis (PCA). The results show the five new factors causing the failure among young entrepreneurs in Telkom University who participate in the Business Plan Competition and Creative Market Exhibition in 2017, are: (1) improper asset and marketing management, (2) unqualified entrepreneurial characteristics, (3) unwell anticipation of capital and regulation pressure, (4) financial and non-financial failures, and (5) ignored by the owner.